A experiência dos cuidados paliativos na perspectiva da equipe de saúde e de familiares de pacientes. - Dantas, Margarida Maria Florêncio (2019)
The present study has focused on palliative care, which represents the treatment of comfort for the relief of the uncomfortable senses of a serious illness that threatens the life of the sick person. The aim of this study is to understand the experience of palliative care from the perspective of the health team and the families of those who are ill. The research followed a qualitative line, and the tools to capture the narratives of the subjects were: the Narrative Interview, the Participating Observation and the Field Diary. These narratives were understood through Discourse Analysis of Foucault's inspiration, which believes that in the speaker's speech contains everything that needs to be said, without lines, in which those who express themselves takes a subject position before the reality they experience. As a result of the analysis of the data, it was observed that both health professionals and family members experience palliation from the place of speech of each one, that is, the place that each one occupies as a subject, suffering the crossings of society, culture and historical time which they are part of.